(untitled) (Al-Qamar, 2025)
This study explores the role of Christian religious institutions in fostering interfaith harmony in Pakistan. Drawing on interviews and an analysis of the statements and services of key Christian leaders—such as Father James Channan, Professor Shaukat Gul, Father Shehzad Khokhar, Pastor Pervez Masih, and Father Haroon Gul—the research highlights their contributions to peacebuilding, social welfare, and the promotion of coexistence within Pakistani society. The findings demonstrate a strong alignment between Christian humanitarian initiatives and Islamic ethical principles, particularly regarding shared values of human dignity, neighborly rights, and social justice. At the same time, the study identifies persistent challenges, including theological differences and external ideological influences. The paper concludes by offering practical recommendations: increased state support, inclusion of interfaith themes in educational curricula, creation of joint dialogue platforms, proactive media engagement, and partnership in welfare projects, counter-extremism strategies, specialized training programs, sustained academic research, and active youth participation as pathways to strengthen interfaith harmony in Pakistan.